2014
DOI: 10.1016/j.lungcan.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Copper transporter CTR1 expression and tissue platinum concentration in non-small cell lung cancer

Abstract: Background Platinum resistance is a major limitation in the treatment of advanced non-small cell lung cancer (NSCLC). We previously demonstrated that low tissue platinum concentration in NSCLC specimens was significantly associated with reduced tumor response. Furthermore, low expression of the copper transporter CTR1, a transporter of platinum uptake was associated with poor clinical outcome following platinum-based therapy in NSCLC patients. We investigated the relationship between tissue platinum concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 27 publications
2
52
0
1
Order By: Relevance
“…Multiple independent research groups in earlier reports identified that reduced intracellular drug accumulation rendered ovarian cancer, non‐small‐cell lung cancer, prostatic cancer, hepatoma cancer, cervical cancer, and colorectal cancer cell lines resistant to cDDP . Recent studies have provided further evidence of the association between cancer tissue platinum concentration and chemotherapy response in muscle‐invasive bladder cancer and non‐small‐cell lung cancer . This evidence suggests that reduced platinum accumulation is an important mechanism of platinum resistance.…”
Section: Introductionmentioning
confidence: 97%
“…Multiple independent research groups in earlier reports identified that reduced intracellular drug accumulation rendered ovarian cancer, non‐small‐cell lung cancer, prostatic cancer, hepatoma cancer, cervical cancer, and colorectal cancer cell lines resistant to cDDP . Recent studies have provided further evidence of the association between cancer tissue platinum concentration and chemotherapy response in muscle‐invasive bladder cancer and non‐small‐cell lung cancer . This evidence suggests that reduced platinum accumulation is an important mechanism of platinum resistance.…”
Section: Introductionmentioning
confidence: 97%
“…A correlation between higher hCTR1 levels and higher platinum drug uptake in tumor cells sensitive to the drug has been reported . The observation that CTR1 expression is upregulated at similar levels in MSI and MSS tumors would suggest a sensitivity of both types of CRC to platinum drugs.…”
Section: Discussionmentioning
confidence: 90%
“…More recently Kim et al . could detect the expression of CTR1 by immunohistochemistry in several samples of nonsmall cell lung cancer and corresponding normal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…As the primary copper influx transporter, CTR1 controls cellular cDDP accumulation. The correlation between higher CTR1 levels and higher platinum drug uptake in tumor cells has been confirmed in a number of studies [9, 12]. CTR1 upregulation can sensitize tumor cells to platinum drugs, while CTR1 downregulation promotes resistance [9].…”
Section: Introductionmentioning
confidence: 93%